AL-TARADUF (SINONIM) DAN KAIDAH PENERAPANNYA DALAM AL-QUR’AN - Muhammad Syarif Hasyim (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
Arabic has several unique features that are different from other languages, one of the uniqueness of Arabic is its mutaradif pronunciation, namely: several pronunciations that have the same meaning. It's just that its application in the Qur'an is still pro and contra between the scholars; some admit and are found in the Qur'an, but not a few also deny its existence in the Qur'an, but still admit that it is in language. Those who deny it believe that every pronunciation must have a specific meaning not shared by other accents. In contrast, those who admit it argue, among other things, that the fact that in Arabic, there are mutaradif pronunciations, of course, may happen in the Qur'an because the Qur'an is reveal in Arabic. It is one of the elements of beauty. And miracles of the language of the Qur'an. Therefore, to bridge the existence of Al-Taraduf. in the Al-Qur'an, the scholars have established several rules to guide in understanding and exploring the implied meaning of the content in the Al-Qur'an, including the rules they set are the rules of Al-Taraduf.